Civil Society in Iraqi Kurdistan: a historical perspective - Jalal Nori, Abdulwahed; Jamal Mohammed Ameen Hussein, amal Mohammed Ameen Hussein (2022)
This article analyses the history of civil society organisations (CSOs) in Iraqi Kurdistan, which has passed through several stages due to the attitudes of the political systems that have ruled Iraq. In this regard, under the rule of several Iraqi governments, CSOs in Iraqi Kurdistan were banned and repressed from their inception until 1991 because they were a living part of the Kurdish society, which was in the process of liberation. However, since the establishment of the Kurdistan Regional Government (KRG), they have been given some freedom to work, which has led to their growth. Nevertheless, CSOs have faced many internal and external obstacles in recent years. This study is based on a scientific method and uses historical and political analysis to show the historical reality of CSOs in Iraqi Kurdistan. Despite having a long history of difficult periods, since 1991, with the establishment of the first cabinet of the KRG, CSOs’ activities have increased. Nevertheless, in recent years, CSOs have faced many internal and external obstacles, though they continue to grow and remain agile.